Machine Learning Applications in E-commerce Using Recommendation Algorithms (International Journal of Food and Nutritional Sciences, 2022)
A new time in e-commerce has arrived due to the integration of machine learning and Recommen-dation algorithms, an important element of machine learning's connection with online commerce, which is changing this industry. These algorithms make use of data analytics to provide users with customized purchasing experiences that improve user retention, satisfaction, and conversion rates. In an era of information overload, customization is the key to making the process of finding products faster. Systems for recommendation make product suggestions by studying user actions and choices, increasing engagement, and increasing the number of sales.These algorithms additionally improve the management of stocks by accurately projecting consumption and reducing oversupply and understock issues. Also, they're important in the security of transactions, confidence among customers, and scam prevention and detection. The systems for recommendations boost loyalty to brands and repeat economics by continuously providing personalized suggestions and offers. Artifi-cial machine learning and recommendation algorithms will continue to be crucial tools for companies aiming to stay competitive and deliver outstanding customer service as e-commerce grows. This article thoroughly examines these uses these uses in-depth, highlighting their importance and practical usefulness.